2023
DOI: 10.1021/acs.jmedchem.3c01372
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of Novel Dual-function Antifungal Inhibitors and Covalent Organic Framework Carriers Based on the Infection Microenvironment

Yating Liu,
Qingpeng Wang,
Shuai Yu
et al.

Abstract: In this study, PD-L1 and CYP51 were selected as key dual-target enzymes, which play an important role in the process of fungal proliferation and immune suppression. A series of novel bifonazole dual-target compounds were designed through the method of fragment combination. Their chemical structure was synthesized, characterized, and evaluated. Among them, the compounds (10c-1, 14a-2, 17c-2) exhibited excellent antifungal and antidrug-resistant fungal activity in vitro. In particular, the preferred compound 14a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The microenvironment of fungal infection (pH values: 4.0–6.5) exhibited the acidic characteristics, stemming from inflammatory responses and the metabolites of pathogenic fungi. , The degradable covalent organic framework (COF) was constructed as the delivery carrier, which could improve the bioavailability of preferred compound 18b-2 and eliminate its adverse reactions. In the process, 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde (Tp) and terephthalo-hydrazide (Bch) were selected as starting materials; they could generate the hydrazone COF (Tp-Bch) skeleton through condensation reactions in the binary solvent system (1,4-dioxane/trimethylbenzene), and the corresponding structural characterization was verified using Fourier transform infrared (FT-IR) spectroscopy and powder X-ray diffraction (PXRD), which suggested that the COF (Tp-Bch) skeleton with the specific crystal structure has been properly constructed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The microenvironment of fungal infection (pH values: 4.0–6.5) exhibited the acidic characteristics, stemming from inflammatory responses and the metabolites of pathogenic fungi. , The degradable covalent organic framework (COF) was constructed as the delivery carrier, which could improve the bioavailability of preferred compound 18b-2 and eliminate its adverse reactions. In the process, 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde (Tp) and terephthalo-hydrazide (Bch) were selected as starting materials; they could generate the hydrazone COF (Tp-Bch) skeleton through condensation reactions in the binary solvent system (1,4-dioxane/trimethylbenzene), and the corresponding structural characterization was verified using Fourier transform infrared (FT-IR) spectroscopy and powder X-ray diffraction (PXRD), which suggested that the COF (Tp-Bch) skeleton with the specific crystal structure has been properly constructed.…”
Section: Resultsmentioning
confidence: 99%
“…The microenvironment of fungal infection (pH values: 4.0−6.5) exhibited the acidic characteristics, stemming from inflammatory responses and the metabolites of pathogenic fungi. 24,37 The degradable covalent organic framework (COF) was constructed as the delivery carrier, which could improve the bioavailability of preferred compound 18b-2 and eliminate its adverse reactions.…”
Section: Flow Cytometry Analysis Of Fungalmentioning
confidence: 99%
See 2 more Smart Citations
“…To further validate the binding ability between the perfected compounds 9a-2, 12a-2, and 12b-1 with the PD-L1 receptor, their affinity data were obtained though surface plasmon resonance (SPR) experiments. 33 During the process, their binding statuses are continuously monitored and summarized in Figure 6. The KD values of these preferred compounds 9a-2, 12a-2, and 12b-1 were located in the range from 8.77 e −9 to 4.01 e −8 , indicating they exerted highly efficient affinity with PD-L1.…”
Section: Affinity Evaluationmentioning
confidence: 99%